Disseminated Tuberculosis Mimicking as Crohn’s Disease in a Paediatric Patient - Elizabeth Feenstra; Yentl Driesen; Nicolette Moes; Nathalie Jouret; Koen Vanden Driessche (Case Reports in Infectious Diseases)
Tuberculosis is an important infectious disease for children worldwide. The clinical presentation of tuberculosis in children is diverse and, depending on the affected organs, it is often accompanied with nonspecific symptoms that can mimic other diseases. In this report, we present a case of disseminated tuberculosis in an 11-year-old boy with intestinal followed by pulmonary involvement. The diagnosis was delayed for several weeks due to the clinical picture which was mimicking Crohn’s disease, the known difficulties in diagnostic tests and the improvement on meropenem. This case demonstrates the importance of a detailed microscopic examination of gastrointestinal biopsies and the tuberculostatic effect of meropenem which physicians should be aware of.